Computational Aspects of Quaternionic Polynomials - Part II: Root-Finding Methods - Falcão, M. I. (2018)
This article explores the numerical mathematics and visualization capabilities of Mathematica in the framework of quaternion algebra. In this context, we discuss computational aspects of the recently introduced Newton and Weierstrass methods for finding the roots of a quaternionic polynomial.